Effects of fatigue loading and alkali–silica reaction on the mechanical behavior of pavement concrete. (22nd May 2017) - Wiedmann, Andreas; Weise, Frank; Kotan, Engin; Müller, Harald S.; Meng, Birgit
Abstract : The primary aim of this paper is to analyze the impact of mechanical pre‐damage and alkali–silica reaction (ASR) on the fracture mechanical properties of pavement concrete. For this purpose, a four point bending test was applied to large format beams to produce a defined level of cyclic pre‐damage. The fatigue‐induced concrete degradation process was simultaneously recorded using a testing procedure specifically developed for the purpose. In addition, fatigue‐induced cracks on extracted drilling cores were spatially visualized and quantified using micro X‐ray 3D‐computed tomography (3D‐CT). The storage of the small‐format test specimens, with and without cyclic pre‐damage, in an ASR‐conducive environment showed that pre‐damage leads to an increase in ASR damage processes. Subsequent structural mechanical investigations on small format specimens with and without pre‐damage show that fatigue loading and ASR significantly influence fracture mechanical parameters of the concrete.